Influence of Demographic Factors on Presentation, Symptoms and Function in Carpal Tunnel Syndrome - Justyna Napora; Pawel Korolkiewicz; Agnieszka Blacha; Agata Kreńska; Tomasz Mazurek (Healthcare, 2026)
Background: Carpal tunnel syndrome (CTS) is the most common peripheral nerve entrapment disorder and a leading cause of pain, sensory disturbances, and functional impairment of the hand. Although carpal tunnel release (CTR) is an established treatment, the influence of demographic characteristics on symptom severity and postoperative functional recovery remains incompletely understood. Aim: This study assessed short-term functional improvement following carpal tunnel release and explored associations between demographic characteristics and patient-reported outcomes before and after surgery. Materials and Methods: Thirty-two adults with electrophysiologically and ultrasonographically confirmed CTS underwent minimally invasive carpal tunnel release. Functional outcomes were assessed preoperatively and three months postoperatively using the Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) questionnaire and the Boston Carpal Tunnel Questionnaire (BCTQ). Demographic variables, including sex, education, occupation, place of residence, symptom duration, dominant hand, and primary presenting complaint, were analysed using non-parametric statistical methods. Results: Significant postoperative improvement was observed in both outcome measures. Mean QuickDASH scores improved by approximately 54.2%, while total BCTQ scores improved by approximately 42% (both p < 0.001). Most demographic variables showed no statistically significant association with postoperative outcomes. Sex was significantly associated with both preoperative and postoperative QuickDASH scores, while the symptomatic hand was significantly associated with preoperative QuickDASH scores. No statistically significant associations were identified between the analysed demographic variables and BCTQ scores. Twenty-six patients (81.2%) reported clinical improvement. Conclusions: Minimally invasive carpal tunnel release was associated with substantial short-term improvement in symptoms and hand function at three months. Exploratory analyses identified statistically significant associations between selected demographic characteristics and patient-reported outcomes; however, the limited subgroup sizes preclude definitive conclusions regarding independent demographic effects. Larger cohorts with longer follow-up and multivariable analysis are required to confirm these findings.